Psychological Dynamics in Long-Distance Relationships: Anxious and Avoidant Attachment Styles as Predictors of Relationship Satisfaction in Early Adulthood - Hartono, Shelly Patricia; Mardi Rahayu, Maria Nugraheni (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Long-distance relationships are often considered to have a lower success rate compared to close-distance relationships. Attachment style is one of the factors that influence relationship satisfaction. This study aims to determine the correlation between anxious and avoidant attachment styles with relationship satisfaction in early adults who are in long-distance relationships. The subjects in this study were early adults who were in long-distance relationships with a sample of 204 respondents obtained through accidental sampling techniques. This study used a quantitative method with a measurement scale used Experiences in Close Relationships Revised (ECR-R) and Relationship Assessment Scale (RAS). The research data were analyzed using the Spearman Rank correlation technique. The results showed that there was a significant negative relationship between anxious and avoidant attachment styles with relationship satisfaction in early adults who were in long-distance relationships with a correlation coefficient value of anxious attachment style of r = -0.233 (p = 0.001) and for the correlation coefficient value of avoidant attachment style of r = -0.584 (p = 0.000) which indicates a negative relationship with relationship satisfaction. This means that the higher the anxious and avoidant attachment style, the lower the relationship satisfaction, and vice versa, the lower the anxious and avoidant attachment style, the higher the relationship satisfaction in young adults in long-distance relationships.Hubungan jarak jauh sering kali dianggap memiliki tingkat keberhasilan yang lebih rendah dibandingkan dengan pacaran jarak dekat. Gaya kelekatan merupakan salah satu faktor yang berkaitan dengan kepuasan hubungan. Penelitian ini bertujuan untuk mengetahui korelasi gaya kelekatan cemas dan menghindar dengan kepuasan hubungan pada dewasa awal yang sedang menjalani hubungan jarak jauh. Subjek dalam penelitian ini adalah dewasa awal yang sedang menjalani hubungan jarak jauh dengan sampel berjumlah 204 responden yang diperoleh melalui teknik accidental sampling. Penelitian ini menggunakan metode kuantitatif dengan skala pengukuran yang digunakan Experiences in Close Relationships Revised (ECR-R) dan Relationship Assessment Scale (RAS). Data penelitian dianalisis dengan menggunakan teknik korelasi Rank Spearman. Hasil penelitian menunjukkan bahwa terdapat hubungan negatif yang signifikan antara gaya kelekatan cemas dan menghindar dengan kepuasan hubungan pada dewasa awal yang menjalani hubungan jarak jauh dengan nilai korelasi koefisien gaya kelekatan cemas sebesar r= -0.233 (p= 0,001) dan untuk nilai korelasi koefisien gaya kelekatan menghindar sebesar r= -0,584 (p= 0,000) yang menunjukkan arah hubungan negatif dengan kepuasan hubungan. Artinya, semakin tinggi gaya kelekatan cemas dan menghindar maka semakin rendah kepuasan hubungan, dan sebaliknya, semakin rendah gaya kelekatan cemas dan menghindar maka semakin tinggi kepuasan hubungan pada dewasa awal yang menjalani hubungan jarak jauh.